Reducing food waste at school canteens : the behaviour of school communities - Saraswathy Kasavan,; Sumiani Yusoff,; Nurul Izzati Mohd Ali,; Nadia Azia Masarudin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Efforts to achieve effective food waste management at the school level can be enhanced by knowing the consumers' behavioural aspects, such as the determinants, perception, and driving force behind food waste. However, most of the previous studies tend to focus on household behavioural aspects in food waste management rather than in the context of hospitality, much less at the school canteen level. The objective of this study is to investigate the behaviours of food waste management among school communities. A questionnaire was distributed to 692 primary school students, secondary school students, and teachers in ten public schools in Hulu Selangor. Interviews were conducted with canteen managers, and observations were made during the fieldwork. From the findings, it can be concluded that 81% of primary school students, 72% of secondary school students, and 91% of teachers are aware of the importance of reducing food waste and personal responsibility in protecting the environment. However, there is a lack of knowledge in food waste management in a sustainable manner, particularly about converting the waste into compost. Meanwhile, the canteen staff could manage kitchen food waste through systematic and effective management, but they are still unable to control the plate waste generated by the students and teachers. These findings may provide necessary information for improving food waste management at the school level, which helps address the guidelines and recommendations that would have a better impact on reducing FW generation, which may be applicable in Malaysia and other countries well.